Lentiviral gene rescue of a Bernard–Soulier mouse model to study platelet glycoprotein Ibβ function. (14th July 2016) - Strassel, C.; Bull, A.; Moog, S.; Receveur, N.; Mallo, L.; Mangin, P.; Eckly, A.; Freund, M.; Dubart‐Kupperschmitt, A.; Gachet, C.; Lanza, F.
Abstract : Essentials A signaling role of glycoprotein (GP)Ibβ is postulated but not formally demonstrated in platelets. Lentiviral‐mediated rescue in knock‐out mice can be used to evaluate GPIbβ function in vivo . Transduction of the native subunit corrected the main defects associated with GPIb‐IX deficiency Deletion of intracellular 159–170 segment increased thrombosis, 150–160 removal increased bleeding. Summary: Background: The platelet glycoprotein (GP)Ib‐V‐IX complex is required for normal hemostasis and megakaryopoiesis. A role in GPIb‐dependent responses has been ascribed to the less well characterized GPIbβ subunit using a specific antibody and GPIb‐IX transfected cells. Objectives: Our aim was to evaluate, in vivo, the role of the GPIbβ in hemostasis and thrombosis. Methods: GPIbβ null Sca‐1 + progenitors transduced with viral particles harboring hGPIbβ were transplanted into lethally irradiated GPIbβ −/− recipient mice. Results: hGPIbβ transplanted into the bone marrow of GPIbβ null mice rescued GPIb‐IX expression in 97% of circulating platelets. These platelets efficiently bound von Willebrand factor (VWF) and extended filopodia on a VWF matrix, demonstrating the restoration of GPIb‐dependent adhesive and signaling properties. These mice exhibited less severe macrothrombocytopenia and had normal tail bleeding times as compared with GPIbβ null mice. This strategy was employed to manipulate and evaluate the role of the GPIbβ intracellular domain. Removal of the membrane proximal segment (Δ 150–160 ) decreased GPIb‐IX expression by 43%, confirming its involvement in receptor assembly and biosynthesis, and resulted in increased bleeding times and decreased thrombosis in a mechanical injury model in the aorta. On the other hand, deletion of the C‐flanking 159–170 segment allowed normal GPIb‐IX expression, VWF‐dependent responses and bleeding times, but resulted in enhanced arterial thrombosis. Conclusion: This pointed to a repressor role of GPIbβ in thrombus formation in vivo that was not predicted in studies of heterologous cells. These results highlight the utility of this lentiviral strategy for the structure‐function evaluation of GPIb‐IX in platelets.